PENGARUH DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG KE OBJEK WISATA ALAHAN PANJANG RESORT DANAU DIATAS KABUPATEN SOLOK - Yolanda, Fanny; Yuliana, Yuliana; Pramudia, Heru (Journal of Home Economics and Tourism, 2017)
This study aims to determine the effect of tourist attraction to the visitor decision at Alahan Panjang Resort Danau Diatas. This type of research is quantitative descriptive form of the causal connection. The population in this study is the average number of guest visited 3.107 people per month. The number of samples in this study are numbered 97 people were tajen using the formula Riduwan. The sampling technique is non probability sampling., (purposive sampling). Collecting data using a questionnaire based on Likert Scale which has proven is validity and reliability. Result of simple linear regression analysis obtained Fcount 113.831 with sig 0,000<0,05, then the variable can explain the variabel tourist attraction with R Square of 0,0545. This means that tourist attraction affects to the visitor decision by 54,5% and 45,5% influenced by other factors.Keyword:Tourist Attraction, Visitor Decision